2009
DOI: 10.1007/s00268-009-9981-x
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Surgical Disease: Does the Literature Reflect the Scope of the International Crisis?

Abstract: This report summarizes what little is known in terms of numeric estimates for the global burden of surgical disease. Globally, access and availability of surgical care in developing countries remains scarce, but the problem is receiving more attention for the first time in surgical circles. Much work remains in the effort to obtain reliable estimates of the global burden of surgical disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 64 publications
0
41
0
Order By: Relevance
“…There are several possible explanations for low output. First, there is an observed shortage of trained researchers and orthopaedic surgeons and limited funding and infrastructure for conducting and publishing clinical research [1,31]. Assessing research capacity in the developing world is a necessary first step in addressing these limitations [10,29].…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for low output. First, there is an observed shortage of trained researchers and orthopaedic surgeons and limited funding and infrastructure for conducting and publishing clinical research [1,31]. Assessing research capacity in the developing world is a necessary first step in addressing these limitations [10,29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a significant variability between estimations provided by specialized burn physicians and less experienced medical professionals [18][19][20][21]. Given the dearth of surgeons and health care professionals in sub-Saharan Africa, TBSA estimation is often inaccurate and unreliable, as specialized burn training is typically limited or altogether non-existent [22][23][24]. This highlights the need for implementing simple strategies aimed at improving outcome of management of burn-injured patients [25].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Although little is factually known of the burden of surgical diseases,[2] 11% of the global burden of diseases may be attributable to surgically treatable causes. [3] In Africa, the Bellagio report of 2007 concluded that a significant burden of disease is attributable to surgical conditions in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%